2014
DOI: 10.3390/ijms150711495
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to AT1 Receptor Autoantibodies during Pregnancy Increases Susceptibility of the Maternal Heart to Postpartum Ischemia-Reperfusion Injury in Rats

Abstract: Epidemiological studies have demonstrated that women with a history of preeclampsia have a two-fold increased risk of developing cardiovascular diseases in later life. It is not known whether or not this risk is associated with angiotensin II receptor type 1 autoantibody (AT1-AA), an agonist acting via activation of AT1 receptor (AT1R), which is believed to be involved in the pathogenesis of preeclampsia. The objective of the present study was to confirm the hypothesis that AT1-AA exposure during pregnancy may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…Rats administered AT1-AA during pregnancy displayed no differences in cardiac function as compared with normal pregnant rats 16 weeks postpartum in a study conducted by Wang et al 145 However in this study, there were several morphological changes in cardiomyocytes, increased collagen content, and changes in the myocardium structure of rats administered the AT1-AA during pregnancy. 145 These changes were prevented when losartan was administered along with AT1-AA during pregnancy. 145 These data taken together suggest that the AT1-AA may play a pivotal role in the development or pathogenesis of cardiovascular dysfunction and CVDs in the mother.…”
Section: Chronic Inflammation Is a Common Thread That Could Contributcontrasting
confidence: 62%
See 1 more Smart Citation
“…Rats administered AT1-AA during pregnancy displayed no differences in cardiac function as compared with normal pregnant rats 16 weeks postpartum in a study conducted by Wang et al 145 However in this study, there were several morphological changes in cardiomyocytes, increased collagen content, and changes in the myocardium structure of rats administered the AT1-AA during pregnancy. 145 These changes were prevented when losartan was administered along with AT1-AA during pregnancy. 145 These data taken together suggest that the AT1-AA may play a pivotal role in the development or pathogenesis of cardiovascular dysfunction and CVDs in the mother.…”
Section: Chronic Inflammation Is a Common Thread That Could Contributcontrasting
confidence: 62%
“… 145 These changes were prevented when losartan was administered along with AT1-AA during pregnancy. 145 These data taken together suggest that the AT1-AA may play a pivotal role in the development or pathogenesis of cardiovascular dysfunction and CVDs in the mother.…”
Section: Chronic Inflammation Is a Common Thread That Could Contributmentioning
confidence: 99%
“…A previous study also reported that mitochondrial structure plays an important role in cardiac function (32). Degradation in mitochondrial structure results in a progressive increase in mitochondrial Ca 2+ sequestration and mitochondrial depolarization, finally leading to cardiac dysfunction (33).…”
Section: Discussionmentioning
confidence: 91%
“…The AT1-AAs IgG was prepared from the sera of 5 ACS patients with higher AT1-AAs titer separately, purified by affinity chromatography as described previously [ 11 ]. Briefly, the immunoglobulin fractions were loaded on a Sepharose 4B CNBr-activated gel, to which the peptide corresponding to AT1-EC2 was covalently linked [ 20 ]. The antibodies were adsorbed on the affinity column and eluted with 3 mol/L potassium thiocyanate.…”
Section: Methodsmentioning
confidence: 99%